2021
DOI: 10.3389/fpls.2021.706679
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Application of Non-mature miRNA-Encoded miPEP164c Inhibits Proanthocyanidin Synthesis and Stimulates Anthocyanin Accumulation in Grape Berry Cells

Abstract: Secondary metabolic pathways in grape berries are tightly regulated by an array of molecular mechanisms, including microRNA-mediated post-transcriptional regulation. As recently discovered, before being processed into mature microRNAs (miRNAs), the primary transcripts of miRNAs (pri-miRNAs) can encode for small miRNA-encoded peptides (micropeptides – miPEPs) that ultimately lead to an accentuated downregulation of the respective miRNA-targeted genes. Although few studies about miPEPs are available, the discove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…As the EAR motif by forming complex with chromatin‐altering proteins regulates the expression of different genes at epigenetic level (Kagale & Rozwadowski, 2011), and in our analysis, the C2 motif, a type of EAR motif is present in all identified MaMYBPR proteins, these chromatin‐altering proteins might form a complex with these repressors to modulate their repressor activity in banana. The grapevine gene VvMYBPA1 transcripts are targeted by microRNA164c (miR164c) for mRNA cleavage, resulting in lower expression of LAR and ANR , and therefore lower proanthocyanidin accumulation in grape berries (Vale et al ., 2021). The varying accumulation of the transcripts of regulatory R2R3‐MYB genes in banana tissues may be attributed to these regulators acting at different levels, which are yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…As the EAR motif by forming complex with chromatin‐altering proteins regulates the expression of different genes at epigenetic level (Kagale & Rozwadowski, 2011), and in our analysis, the C2 motif, a type of EAR motif is present in all identified MaMYBPR proteins, these chromatin‐altering proteins might form a complex with these repressors to modulate their repressor activity in banana. The grapevine gene VvMYBPA1 transcripts are targeted by microRNA164c (miR164c) for mRNA cleavage, resulting in lower expression of LAR and ANR , and therefore lower proanthocyanidin accumulation in grape berries (Vale et al ., 2021). The varying accumulation of the transcripts of regulatory R2R3‐MYB genes in banana tissues may be attributed to these regulators acting at different levels, which are yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of anthocyanins was performed using 100 mg of grape berry cells from each experimental condition as described in Vale et al (2021). The extraction process was performed using 90% (v/v) methanol and 10% (v/v) deionized water.…”
Section: Quantification Of Anthocyaninsmentioning
confidence: 99%
“…In this study, ghy-miR156 accumulated to high levels during S6, which implies an association with anthocyanin biosynthesis. In addition, miR164-encoded peptides (miPEP164), which are encoded by primary transcripts of miR164, positively regulate the proanthocyanidin biosynthetic pathway [97]. In this study, levels of the mature sequence of ghy-miR164 were shown to increase with ray petal growth, and thus it will be interesting to investigate the role of miPEP164 in the anthocyanin biosynthesis pathway in gerbera ray petals.…”
Section: Correlation Analysis Of Differentially Expressed Mirnas and ...mentioning
confidence: 88%